The contextual compass : a literary-historical study of three British women’s travel writing on Africa, 1797 – 1934 - Visser, Liezel (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (English Studies))--University of Stellenbosch, 2009.